Hubungan Dukungan Keluarga dengan Pemberian ASI Ekslusif pada Bayi Usia 0-6 Bulan - Ria Risti Dewi; Junendri Ardian; Wiwin Lastyana (Program Studi Gizi, Universitas Bumigora, 2023)
ABSTRACT The relationship between family support and exclusive breastfeeding for infants aged 0-6 months in the working area of the Karang Taliwang Health Center Ria Risti Dewi Background : Breast milk is the first food for newborns, variousscientific points of view can be proven that breast milk is the best and most ideal baby food. Although there are many known benefits of exclusive breastfeeding, there are still many mothers who do not breastfeed exclusively, many factors that influence breastfeeding are not Exclusively, one of which is support from the family, which is to provide information, advice and attention that makes mothers feel comfortable and calm in the process of breastfeeding. Objective : The purpose of this study was to determine the relationship between family support and exclusive breastfeeding for infants aged 0-6 months in the working area of the Karang Taliwang Mataram Health Center. Method : The method in this study is quantitative with a cross sectional approach. The sample in this study was 63 respondents, the sampling technique in this study was purposive sampling. Data analysis using chi square test. Results : The results of this study showed no meaningful relationship of emotional support (p = 0.632), no relationship of instrumental support (p = 0.727), there was an association of assessment support (p = 0.008), there was an association Information support (p = 0.030) with exclusive breastfeeding for infants aged 0-6 months in the working area of the Karang Taliwang Mataram Health Center. Conclusion : The conclusion in this study is that there is no significant relationship between emotional support and instrumental support and exclusive breastfeeding, while in assessment support And information there is a significant relationship with exclusive breastfeeding in infants aged 0-6 bulam. Keywords : Exclusive Breastfeeding, Family Support